(Cria)tive Listening: proposals for the development of music listening in basic education (Foro de Educacion, 2017)
During the years 2015 and 2016 we coordinated a research entitled Mediated and expanded listening for high school music classes: Dialogues between Murray Schafer and Luciano Berio, which proposed structuring methodological approaches to develop and expand the musical listening of young people who are at school having as a start point the dialogue between listening strategies proposed by Murray Schafer and the work of Luciano Berio. For the construction of a pedagogical-musical approach centered on listening the teaching strategies to expand the listening proposed by Schafer (2011) were mapped as well as four musical pieces by the composer Luciano Berio were analyzed. Our hypothesis was that the use of the teaching strategies proposed by Schafer for the active appreciation of Berio repertoire could enhance the development of a renewed musical listening, which would require from the students and the teacher an extension or a expansion of concepts of what they understand by «music». The results showed that the young participants expressed interest in the contemporary repertoire as they were being instrumentalized by the developed mediation activities. Mediation was carried out through active listening proposals through creative action on the sounds around us and on the selected repertoire. The experience of listening to music is a creative activity and has intensive demands on your exercise. It is an inner process of knowledge and discovery that should be considered central in the training of music teachers.